Doing more while remaining the same? Flood risk governance in Poland. Issue 3 (2nd May 2017) - Matczak, P.; Lewandowski, J.; Choryński, A.; Szwed, M.; Kundzewicz, Z.W.
Abstract : This paper presents how the approaches to flood risk in Poland have evolved over the last 25 years. The reliance on structural defence and on the state as the key responsible actor was challenged by four triggering events: two large floods; the collapse of the communist system; and the European Union accession. The paper reveals that (1) the radical transformation of the political system did not lead to significant changes in flood risk governance; (2) changes in response to disastrous floods are incremental. Despite the pressures, the Polish flood risk governance preserved its core functional characteristics. Until the 1997 flood, it exhibited the exhaustion mode of institutional dynamics, with issue marginalisation and poor financing, while after this flood, the layering‐type mode prevailed, where innovative ideas were accommodated by the established system. The analysis of the Polish flood risk governance dynamics suggests that changes cannot be taken for granted, even facing significant pressures and windows of opportunities.